Structure Design of Parking Building on Delta Areas - Bambang Wuritno (International Conference on Coastal and Delta Areas, 2015)
The case study in this research is Parking building (Tower C), Project Sunter Park View Apartment is a public facility that serves as a parking garage. It located on the Yos Sudarso Street Kav 30A, Sunter Jaya – North Jakarta ( on Delta Areas ). This building consists of 4 floors including the roof plate with a typical floor plan for each level. Floor to floor elevation is 3 meters height, so the total height of the building reach 9 meters height (less than 40 meters height). Review Design Parkingbuilding structure (Tower C) Project Title: